The Spectrum of Bio-electric Activity in Response to Taste Adjectives - Klochkova, O; Pogorelova, I; Startseva, M; Alexandrov, Y; Shabanov, G (KnE Life Sciences, 2018)
Frequency spectra of the induced brain activity function in the range of 0.13 to 27 Hz of 16 female subjects aged 18–20 were studied. The activity was caused by reading of taste adjectives from the screen. The function significantly differs for different hemispheres in the studied frequency range. Frequency shifts ranges in the stimulation (maxima) and inhibition (minima) zones of the brain activity differential function were determined. ANOVA model implemented within the Statistica 10.0 software was used for statistical analysis of the measured data. Keywords: brain bioelectric activity, cognitive processes, induced oscillations, computer interaction